Teologi Paulus Tentang Iman Analisis dan Implementasinya dalam Kehidupan Kristiani Kontemporer - Gebi Armianti; Paulin Patara (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This article explores Paul's theology, focusing on inner transformation in the context of the Christian life. A literature review and analysis of Paul's key verses is used to reimagine the concepts of salvation, life in the Spirit, and new identity in Christ. Through an explorative approach, this journal explores Paul's transformative and practical theology. Two case studies illustrate the concrete impact of Paul's theology in the lives of individuals and church communities. Key conclusions include salvation as a foundation for transformation, moral and practical realization, and the importance of personal experience with Christ. The results of this research open a new understanding of the application of Paul's theology in the daily lives of Christians, contributing to the learning and application of theological concepts in daily spiritual practice.